Severe Systolic Anterior Motion After Aortic Valve Replacement and Cox MAZE Surgery. Issue 7 (23rd May 2016) - den Uil, Corstiaan A.; ter Horst, Maarten; Akin, Sakir; Galema, Tjebbe W.
Abstract: Surgical aortic valve replacement may be complicated by severe dynamic left ventricular outflow tract obstruction and cardiogenic shock in the postoperative period. We present a patient who developed severe anterior motion following aortic valve and Cox MAZE surgery which necessitated a mitral valve replacement. doi: 10.1111/jocs.12763 (J Card Surg 2016;31:429–431)